Banking Marketing Mix between Theory and Application and its Role in Bank Development: a Case Study of North Bank for Finance and Investment (مجلة المنصور, 2023)
is well known that the banking sector has witnessed dramatic changes due to bank competition, globalization and technologies included. Consequently, many new terms and conditions are invented and then applied; banking marketing mix is among these. The present study examines theoretically the seven parameters of this new procedure, and then compared with its field nature. The field case study held in North Bank in Iraq, where interviews and questionnaire are used as measurement tools for managers and employees, respectively. Both have confirmed the fact that supporting the banking services is the most important parameter on this mix. Therefore, the study recommends establishing a unique management for banking services, which in turn expectedly to enhance the services of banks as a whole.